Analisis Efektifitas Laboratorium Manajemen Pemeliharaan Virtual Berdasarkan Tutorial Virtual - surya wijaya, Andi; Mufti Arifin; Erna Shevilia Agustian (FTK UNSURYA, 2025)
Maintenance management is a series of activities that include planning, organizing, program implementation, and control methods for maintenance activities. This study aims to determine whether maintenance management practices can be implemented effectively through a hybrid training method (virtual and offline) that utilizes a maintenance management laboratory. The research stages include understanding the data that must be inputted by technical records, how to read and fill out maintenance logs, and designing virtual tutorials which are then tested on aviation engineering students. In using the virtual tutorial, students input data, calculate aircraft life utilization based on Time Since New (TSN) or Cycle Since New (CSN), and calculate the life of aircraft components with the same parameters. Based on the results of testing the AFML tutorial on 10 aviation engineering students, it was found that 96% of them were able to answer the evaluation questions correctly, with 8 students answering perfectly and 2 students reaching 80% success rate. These results show that the virtual tutorial developed is quite effective and useful in improving students' understanding of maintenance management, especially in the use and analysis of AFML data.